Food safety culture in foodservice operations: a cross-sectional survey and cluster analysis in Malaysia tourist spots - Aifaa, Roslan; Abidin, Ungku Zainal; Fatimah, Ungku; Maimunah, Sanny; Mutalib, Abdul-; Azira, Noor-; Ishak, Che; Adibah, Farah; Karim, Abdul-; Shahrim, Muhammad (Human Resource Management Academic Research Society, 2023)
In the present globalization context, most organizations are dealing with increased diversification of employees and customers. In the context of food safety, the changing demographic profile of food service employees poses a challenge in managing food safety and ensuring safe food handling practices among employees. Therefore, this study aims to examine the segmentation of food safety culture based on diversity factors in food service operations by using cluster analysis. A cross-sectional study was conducted in food service operations in Malaysia's main tourism areas, and a self-administered questionnaire was delivered to 400 food handlers. A two-step cluster analysis identified three clusters based on the perceived level of organization food safety culture. Heterogeneity of diversity factors across the clusters was observed in nationality (?2=7.367, p=0.025), age (?2=17.796, p=0.023), and employment status (?2=13.230, p=0.001). The finding characterized the respondents' organizations in cluster 1 as "experienced communicator", which is comprised of local workers (89.3%) and full-time workers (87.6%). Meanwhile, the respondents' organization was characterized as "diverse adaptor", where the workers were observed to have a high proportion of young adults group aged between 18-34 years old worker (82.6%). The respondents' organizations in Cluster 3 were characterized as "inexperienced support-seeker”, which workers in this cluster were dominated by part-time workers (32.2%) and the young adult group aged between 18-24 years old (50.2%).